Dynamic Distribution and Interaction of the Arabidopsis SRSF1 Subfamily Splicing Factors. Issue 2 (23rd December 2015) - Stankovic, Nancy; Schloesser, Marie; Joris, Marine; Sauvage, Eric; Hanikenne, Marc; Motte, Patrick
Abstract : The RNA-binding domains of Arabidopsis SRSF1 splicing factors are required for nucleocytoplasmic dynamics and protein-protein interactions. Abstract: Ser/Arg-rich (SR) proteins are essential nucleus-localized splicing factors. Our prior studies showed that Arabidopsis ( Arabidopsis thaliana ) RSZ22, a homolog of the human SRSF7 SR factor, exits the nucleus through two pathways, either dependent or independent on the XPO1 receptor. Here, we examined the expression profiles and shuttling dynamics of the Arabidopsis SRSF1 subfamily (SR30, SR34, SR34a, and SR34b) under control of their endogenous promoter in Arabidopsis and in transient expression assay. Due to its rapid nucleocytoplasmic shuttling and high expression level in transient assay, we analyzed the multiple determinants that regulate the localization and shuttling dynamics of SR34. By site-directed mutagenesis of SR34 RNA-binding sequences and Arg/Ser-rich (RS) domain, we further show that functional RRM1 or RRM2 are dispensable for the exclusive protein nuclear localization and speckle-like distribution. However, mutations of both RRMs induced aggregation of the protein whereas mutation in the RS domain decreased the stability of the protein and suppressed its nuclear accumulation. Furthermore, the RNA-binding motif mutants are defective for their export through the XPO1 (CRM1/Exportin-1) receptor pathway, but retain nucleocytoplasmic mobility. We performed a yeast two hybrid screen with SR34 as bait and discovered SR45 as a new interactor. SR45 is an unusual SR splicing factor bearing two RS domains. These interactions were confirmed in planta by FLIM -FRET and BiFC and the roles of SR34 domains in protein-protein interactions were further studied. Altogether, our report extends our understanding of shuttling dynamics of Arabidopsis SR splicing factors.